Laparoscopic Ureteral Reimplantation after Failed Open Surgery: Incorporating the Psoas Hitch Maneuver for Sufficient Tunnel Length - Shumaker, Andrew D.; Kord, Eyal; Dubrov, Vitaly; Bondarenko, Sergey; Visman, Yakatwrina; Stav, Kobi; Zisman, Amnon; Neheman, Amos (European Journal of Pediatric Surgery, 2022)
Background Failure after open ureteral reimplantation has been reported to occur in 2 to 7% of cases. While a second open reconstructive surgery is appropriate in most cases, there are data suggesting similar outcomes utilizing the laparoscopic approach. The objective of this study is to describe a modification and report our experience with laparoscopic ureteral reimplantation after failed open reimplantation reinforced with a psoas hitch.Materials and Methods A retrospective review of pediatric patients who underwent laparoscopic ureteral reimplantation after failed open surgery between September 2012 and April 2018 at three different academic centers was performed. Patient demographics, surgical indications, complications, and outcomes were reviewed. Either ipsilateral ureteral reimplantation with a combined intravesical and extravesical approaches or a cross-trigonal extravesical approach was utilized, depending on the length of the ureter. In all cases, a psoas hitch was performed to gain a longer submucosal tunnel and relieve tension, thus facilitating an efficient antireflux mechanism.Results Seventeen patients underwent a laparoscopic ureteral reimplantation after failed open surgery. Median age at second surgery was 106 months (interquartile range [IQR]: 53–122.5). Ipsilateral ureteral reimplantation with a combined intravesical and extravesical approaches was performed in 11 cases and cross-trigonal extravesical approach in 6 cases. Median ureteral diameter before the redo surgery was 16 mm (IQR: 14.5–18.5) and after surgery was 6 mm (IQR: 3.5–8.5) (p < 0.001). Postoperative mercaptoacetyltriglycine renal scan showed a nonobstructive pattern and stable renal function in all cases.Conclusion Laparoscopic ureteral reimplantation with incorporation of a psoas hitch after failed open reimplantation is safe and effective.
Keywords: laparoscopy; ureteral reimplantation; reflux; megaureter; psoas hitch